Introducing BDNF and SNAI1 as the Crucial Targeted Genes by UV Radiation: Introducing the Crucial Targeted Genes by UV Radiation - Rezaei-Tavirani, Mostafa; Mansouri, Vahid; Arjmand, Babak; Hamzeloo Moghadam, Maryam; Razzaghi, Zahra; Khodadoost, Mahmood; Rezaei-Tavirani, Majid; Ahmadzadeh, Alireza (Journal of Lasers in Medical Sciences, 2022)
Introduction: Due to the widespread penetration of UV radiation in human life, the biological effect of UV radiation is studied through many investigations in the field of medicine. There are many assessments about UV radiation that are concerned with protein-protein interaction (PPI) network analysis. In the present study, a network analysis associated with the complementary evaluation of UV radiation on human primary melanocytes is presented. Methods: The gene expression profiles of the irradiated human primary melanocytes and the control cells were extracted from Gene Expression Omnibus (GEO) and were evaluated via PPI network analysis and action map assessment. Results: 69 significant differentially expressed genes (DEGs) were included in the main component of the PPI network. Brain-derived neurotrophic factor (BDNF), SNAI1, and SOCS1 were highlighted as the top dysregulated and hub genes. Results indicate that BDNF and SNAI1 participate in the regulatory unit including the total hubs and top dysregulated genes. Conclusion: Considerable down-regulation of BDNF and up-regulation of SNAI1 as the two critical targeted genes by UV radiation are accompanied by gross alteration in cell functions.